Konstruksi Bahan Bekas sebagai Media Pembelajaran untuk Menjawab Isu-Isu Lingkungan - Zahid Zufar At Thaariq; Jasmine Nurul Izza; Reno Nurdiyanto; Fikri Aulia; Devi Mariya Sulfa; Dhimas Adhitya Wijanarko (Proceedings Series of Educational Studies, 2023)
The world's environmental problems are never-ending. From carbon emissions, climate change,harmful land expansion to plastic waste. In education, these issues need to be given specialattention. However, there are still relatively few lessons on how to promote environmental issuesin the formal education system. Narrative review literature review is the method used in thisresearch. This article shows (1) how second-hand materials are used as learning media and (2) howteachers and students actively use second-hand materials as personalized learning media.Utilization of second-hand materials in learning is a form of adaptive learning system, one of whichis personalization system. Personalized learning by using second-hand materials facilitatesstudents' ability to solve problems or environmental issues. Thus, this article can be used as analternative reference in the use of second-hand materials as instructional media.